2016
DOI: 10.1111/jcc4.12160
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Interaction and Fast Feedback Predict Perceived Social Support: Using Crawled and Self-Reported Data of Facebook Users

Abstract: The present study examines if Facebooking can contribute to psychological well-being and if so, which aspects of Facebook use could play a significant role. Matching crawled data with self-reported datamotivation, and social network services (SNSs), such as Facebook, seem to provide a handy way to satisfy this basic human need. Then, is this social networking related to gratifying social relationships and psychological well-being? We attempted to answer this question by examining how Facebook users actually in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 51 publications
4
63
0
1
Order By: Relevance
“…Latency may be effective for the person producing a response but not for the one waiting for it. 14,46 In addition, we observed a negative relationship between counseling impact and waiting time before counseling (H3) in accordance with our hypothesis. Previous research has shown that increased waiting time can result in negative responses.…”
Section: Discussionsupporting
confidence: 89%
“…Latency may be effective for the person producing a response but not for the one waiting for it. 14,46 In addition, we observed a negative relationship between counseling impact and waiting time before counseling (H3) in accordance with our hypothesis. Previous research has shown that increased waiting time can result in negative responses.…”
Section: Discussionsupporting
confidence: 89%
“…Kim & Lee, 2011;Liu & Yu, 2013), and college engagement (Gray et al, 2013). Higher levels of Facebook-based social support also predicted lower levels of a wide range of negative outcomes that were also measured, including depression (Frison & Eggermont, 2015, 2016), victimisation (Cole et al, 2017McConnell et al, 2017), and loneliness (K. T. Lee et al, 2013;Seo et al, 2016). There were some notable exceptions to these findings; for example, for persons with little to no social anxiety (Indian & Grieve, 2014), and male adolescent boys (Frison & Eggermont, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Research into social support drawn from Facebook has found that it can have a positive effect on various outcomes. These have included depression (Frison & Eggermont, 2016;Wright et al, 2013), anxiety (Indian & Grieve, 2014), well-being (Huang, 2016), physical health (Cavallo et al, 2014), and loneliness (Seo, Kim, & Yang, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Social support refers to various forms of aid and assistance supplied by family members, friends, neighbors and others, which broadly encompasses a multitude of social interaction (Barrera et al, 1981;Kalsoom, Masood, & Jami, 2017). Social support is also explained in terms of a process of interaction between relationships which improves copping, esteem, belonging, and competence through real or perceived exchanges of physical or psychological resources (Cohen, Underwood &Gottlieb, 2000;Seo, Kim& Yang, 2016).…”
Section: Previous Literature Exhibits Three Styles Of Daydreaming: Pomentioning
confidence: 99%